2015
DOI: 10.3109/00365521.2015.1043640
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound findings predict the recurrence of esophageal varices after endoscopic band ligation: a prospective cohort study

Abstract: Recurrence rate of esophageal varices after EBL is high (47.5%). EUS can clearly depict ECV and has a value in predicting variceal recurrence after EBL; severe peri-ECV and multiple peri-ECV were significant and independent prognostic factors associated with variceal recurrence risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…Prospective studies with large sample sizes are needed to confirm the results and to discern whether endoscopic ultrasound is useful in identifying communicating or collateral vessels. 15 We found that the incidence of retrosternal pain was higher in the sclerotherapy (+) group than in the sclerotherapy (-) group. But the discomfort was mostly mild and temporary, and this could be quite subjective and possibly biased by memory.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Prospective studies with large sample sizes are needed to confirm the results and to discern whether endoscopic ultrasound is useful in identifying communicating or collateral vessels. 15 We found that the incidence of retrosternal pain was higher in the sclerotherapy (+) group than in the sclerotherapy (-) group. But the discomfort was mostly mild and temporary, and this could be quite subjective and possibly biased by memory.…”
Section: Discussionmentioning
confidence: 64%
“…However, the sample size was small, which limits our conclusions. Prospective studies with large sample sizes are needed to confirm the results and to discern whether endoscopic ultrasound is useful in identifying communicating or collateral vessels …”
Section: Discussionmentioning
confidence: 99%
“…The presence of severe peri-ECV (p < 0.001), multiple peri-ECV (p < 0.001), and PFVs (p < 0.014) were related to the variceal recurrence after EVL. 21 Carneiro et al observed the correlation between EUSbased evaluation of paraesophageal varices, azygos vein, and thoracic duct and variceal recurrence within 1 year after variceal eradication in patients with cirrhosis. The presence of larger para-ECV-a variceal diameter of 6.3 mm before EVL and 4 mm after EVL-predicted variceal recurrence.…”
Section: Treatment Of Esophageal Varicesmentioning
confidence: 99%
“…Studies of EUS after EV eradication show that large para‐esophageal veins greater than 5 mm in diameter were predictive of both EV recurrence and bleeding . Additional studies have also shown the number and diameter of perforating veins also play a predictive role for EV recurrence after eradication . Carneiro et al.…”
Section: Eus and Esophageal Varicesmentioning
confidence: 99%